2021
DOI: 10.3390/nu13051449
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentariness, Eating Behaviour and Well-Being during a COVID-19 Lockdown Period in Greek Adolescents

Abstract: Adolescents’ daily life has dramatically changed during the COVID-19 era due to the social restrictions that have been imposed, including closures of schools, leisure centers and sport facilities. The purpose of this study was to examine levels of well-being and mood and their relations with physical (in)activity and eating behaviors in adolescents during a lockdown period in Greece. A total of 950 adolescents (Mean Age = 14.41 years ± 1.63) participated in a web-based survey while education was conducted onli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 39 publications
9
54
1
1
Order By: Relevance
“…Although numerous studies have examined the PA behavior of children and adolescents during the pandemic, only a few of them have reported exact MVPA per minute data, probably due to the limitations of self-report methods. Morres et al [38] found that adolescents in Greece on average spent only 23.9 min per day in moderate-to-vigorous physical activity, while Tulchin-Francis et al [39] revealed for children and adolescents in the United States an amount of 34.7 MVPA minutes per day. In both studies, questionnaires were used to assess PA; however, the findings are similar to our results and demonstrate that the PA of children and youth in many countries clearly declined under the 60 min recommendation of the WHO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous studies have examined the PA behavior of children and adolescents during the pandemic, only a few of them have reported exact MVPA per minute data, probably due to the limitations of self-report methods. Morres et al [38] found that adolescents in Greece on average spent only 23.9 min per day in moderate-to-vigorous physical activity, while Tulchin-Francis et al [39] revealed for children and adolescents in the United States an amount of 34.7 MVPA minutes per day. In both studies, questionnaires were used to assess PA; however, the findings are similar to our results and demonstrate that the PA of children and youth in many countries clearly declined under the 60 min recommendation of the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the research in this field [41][42][43][44][45]; however, current studies show inconsistent results for gender differences in PA during the pandemic. For instance, Tulchin-Francis et al [39] found no significant differences in PA behavior between male and female students, while Moore et al [40], as well as Morres et al [38], reported significant gender differences in PA and sedentary behaviors, with boys scoring higher in PA and lower on sedentary time. As mentioned above, we also found that boys were significantly more physically active than girls during the pandemic or the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 crisis has led to even more unhealthy behaviors and a higher prevalence of overweight and obesity amongst adolescents, emphasizing the need to invest in effective interventions to prevent obesity starting at a young age [ 24 ]. Recently, a study conducted with adolescents during a lockdown period in Greece suggested prioritizing measures to increase physical activity, decrease sedentariness, and improve eating behavior for better well-being [ 25 ]. Findings of a systematic review emphasized the risk of elevated stress among this age group and the need to develop strategies to support families to cope with the current pandemic situation and ensure their children’s healthy development [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its health and economic effects, COVID-19 has a great impact on people’s lifestyles, including activities such as remote education, eating behaviors and physical activity [ 1 , 2 , 3 ]. These changes have direct effects on body weight.…”
Section: Introductionmentioning
confidence: 99%